Strengthening Madrasah Diniyah Quality through School Governance and Advancing SDG 4: A Multi-Site Study in Pasuruan Regency, Indonesia - Iswahyuni Iswahyuni; Sujarwanto Sujarwanto; Amrozi Khamidi (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examine the implementation of school governance in strengthening the quality of Madrasah Diniyah through a multi-site study conducted in three Madrasah Diniyah in Pasuruan Regency, Indonesia. Method: A qualitative multi-site research design was employed involving Madrasah Diniyah Miftakhul Ulum 31, Madrasah Diniyah Takmiliyah Ula Nurul Fityan, and Madrasah Diniyah Roudhotul Hikmah. Data were collected through semi-structured interviews, observations, and document analysis involving principals, teachers, education officials, and community representatives. Data were analyzed using the interactive model of data condensation, data display, conclusion drawing, and cross-site analysis to identify common governance practices. Results: The findings reveal that effective school governance is achieved through the integration of curriculum management, human resource development, infrastructure management, financial accountability, and stakeholder collaboration. Institutional leadership, teacher commitment, active community participation, and government support through the Regional Operational Assistance (BOP) program significantly contribute to improving educational quality. However, limited infrastructure, inadequate digital learning facilities, financial constraints, and restricted instructional time remain major challenges. Despite these limitations, the three Madrasah Diniyah have maintained educational quality through adaptive leadership, transparent governance, and collaborative partnerships with local communities. Novelty: Proposing an integrated school governance framework for Madrasah Diniyah, demonstrating that governance effectiveness is shaped by the interaction of leadership, organizational management, stakeholder participation, and educational accountability. The findings extend school governance theory to non-formal Islamic education while contributing to Sustainable Development Goal 4 (Quality Education) by strengthening governance practices, educational quality, and institutional sustainability.